2022
DOI: 10.1186/s12875-022-01648-4
|View full text |Cite
|
Sign up to set email alerts
|

Model development to improve primary care services using an innovative network of homecare providers (WinCare) to promote blood pressure control among elderly patients with noncommunicable diseases in Thailand: a prospective cohort study

Abstract: Background Thailand has been rapidly approaching an aging society in conjunction with an increase in noncommunicable diseases (NCDs) especially hypertension and type 2 diabetes. Demographics and epidemiologic transitions create several challenges to the health system in Thailand in the case of long term care policies, in particular, modality to support home care. Therefore, the model development to facilitate primary care home services for elderly patients with NCDs using an innovative network … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Our results reported that there was no significant difference in mean change in BP at a twenty-week follow-up from baseline between intervention and control groups. However, a decrease in SBP and DBP over a 20-week follow-up among intervention participants was pinpointed, which is compatible with the related study in Thai patients with NCDs [ 27 ]. In the present study, the VHV also explored the adverse psychological and physical effects related to the weight-loss program.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Our results reported that there was no significant difference in mean change in BP at a twenty-week follow-up from baseline between intervention and control groups. However, a decrease in SBP and DBP over a 20-week follow-up among intervention participants was pinpointed, which is compatible with the related study in Thai patients with NCDs [ 27 ]. In the present study, the VHV also explored the adverse psychological and physical effects related to the weight-loss program.…”
Section: Discussionsupporting
confidence: 88%
“…The well-trained VHV of the weight-loss program visiting the intervention participants at home weekly may simplify the maintenance of a hypocaloric diet and self-weighing with records. The related studies in Thailand and the UK may support this finding that well-trained providers act as social supporters to improve health outcomes [ 27 , 47 ]. The VHV in the weight-loss program in this study stand for the community health workers who support healthcare providers at the local primary care units in rural communities.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations